Human resource management and industrial relations in multinational corporations in and from China: Challenges and new insights. Issue 5 (26th August 2019) - Cooke, Fang Lee; Liu, Mingwei; Liu, Leigh Anne; Chen, Chao C.
Abstract: The purpose of this article is to provide an overview on the state of research in the field in human resource management (HRM) issues in multinational corporations (MNCs) in and from China. We integrate previous studies from multiple disciplines to articulate the contextual importance of research on this topic, and suggest overarching themes to expand the field of research. HRM research in the intercultural, interinstitutional context of MNCs in and from China has the potential to provide contextualized insights for longstanding debates in the field such as HRM standardization versus localization and convergence versus divergence and contextual factors behind these patterns. To this end, we call for future research to center on the changing cultural, institutional, technological, and globalization context in understanding HRM and industrial relations issues in these MNCs. Practically, knowledge in this area can help global managers and top management teams in multinational organizations navigate various context complexity, foster more productive coordination and cooperation across borders, and gain legitimacy and MNCs in and from China additional competitive edge in the global marketplace.